2009
DOI: 10.1161/hypertensionaha.109.133819
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Antihypertensive Treatment on the Retinal Microcirculation

Abstract: Changes in the retinal microcirculation are associated with hypertension and predict cardiovascular mortality. There are few data describing the impact of antihypertensive therapy on retinal vascular changes. This substudy of the Anglo-Scandinavian Cardiac Outcomes Trial compared the effects of an amlodipine-based regimen (373 patients) with an atenolol-based regimen (347 patients) on retinal microvascular measurements made from fundus photographs. The retinal photographs were taken at a stage in the trial whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
1
39
0
1
Order By: Relevance
“…Lundberg et al have reported that following focal/grid laser treatment of DMO, the macular arteriole and venule diameters decreased [103], and Wickremasinghe et al reported a significant narrowing effect on both retinal arteriolar and venular calibres in patients with DMO in response to intravitreal triamcinolone [104]. Studies have also demonstrated regression of retinal vascular changes in response to blood pressure reduction and that regression differs between different antihypertensive regimens [105][106][107].…”
Section: Retinal Vasculature Measurements In Clinical Practicementioning
confidence: 99%
“…Lundberg et al have reported that following focal/grid laser treatment of DMO, the macular arteriole and venule diameters decreased [103], and Wickremasinghe et al reported a significant narrowing effect on both retinal arteriolar and venular calibres in patients with DMO in response to intravitreal triamcinolone [104]. Studies have also demonstrated regression of retinal vascular changes in response to blood pressure reduction and that regression differs between different antihypertensive regimens [105][106][107].…”
Section: Retinal Vasculature Measurements In Clinical Practicementioning
confidence: 99%
“…Studies have demonstrated regression of hypertensive retinopathy signs in response to BP reduction and that regression is different in response to different antihypertensive regimens (eg, angiotensin-converting enzyme inhibitors seem to have a more favorable effect on the retinal vasculature). [109][110][111] Changes in retinal vasculature, markers of hypertensive state, may act as therapeutic targets capable of reflecting the effectiveness of antihypertensive drug treatment in controlling elevated BP values. Nevertheless, data describing the impact of antihypertensive therapy on retinal vascular changes are still lacking.…”
Section: Can Retinal Vascular Imaging Be a Surrogate Measure To Evalumentioning
confidence: 99%
“…68 Nevertheless, in comparison with bblockers, the calcium antagonists show better remodeling response in retinal microvasculature attributed to its vasodilatory action. 69 Finally, a retinal assessment may be useful to screen for patients with white-coat hypertension or masked hypertension. These patients are reported to represent How does hypertension affect your eyes?…”
Section: Genetic Associationsmentioning
confidence: 99%